‘Risk-benefit’ assessment for comprehensive safety evaluation of Chinese patent medicines containing four common toxic ingredients: an analysis of clinical risk factors - Zhang, Nan; Zhong, Changming; Liu, Guoxiu; Li, Siyu; Lin, Li; Wei, Namin; Song, Yu; Wan, Xiaoqing; Wang, Yanping; Wang, Yongyan; Wu, Wanlin; Qian, Zhongzhi; et al. (Frontiers in Pharmacology, 2024)
Background: Chinese patent medicines are specialty preparations in China that are produced using traditional prescriptions processed by modern pharmaceutical technology. They contain complex ingredients and much attention is paid to their clinical safety. Demonstrating the clinical safety of Chinese patent medicines containing toxic ingredients in modern pharmacological studies has become one of the urgent issues to be solved for the safe use of clinical medicines.The aim of this research is to evaluate the safety of Chinese patent medicines containing toxic ingredients by applying the risk-benefit assessment method.Additionally, a database of 'toxic ingredients -toxic Chinese herbal medicines-adverse reactions' will be established to explore the relationship between toxic ingredients and adverse reactions. This will lay the foundation for the rational clinical use of Chinese patent medicines containing toxic ingredients.Methods: 1) Establish a database of 'toxic Chinese herbal medicines -toxic ingredients -toxic Chinese patent medicines' to count the Chinese patent medicines containing toxic ingredients in the 2020 edition of Chinese Pharmacopoeia. 2) Filtered the clinical studies, extracted the drug-related ADEs, and analyzed the characteristics and correlations of these ADEs. 3) Finally, this section summarizes the causes of ADEs related to Chinese patent medicines containing toxic ingredients and extracts the main risk factors to provide a reference for further study.Outcomes: 1) There are four main types of Chinese patent medicines containing toxic ingredients. These include medicines with diester aconitine metabolites, mineral composition, Araceae metabolites, and hydrogen cyanide. 2) Digestive system, skin and its appendages, and allergic reactions were the main types of ADEs related to four types of Chinese patent medicines containing toxic ingredients. 3) There are four primary risk factors associated with the clinical use of Chinese patent medicines containing toxic ingredients: medicine, medication, individual and regulatory factors.